The Anterior Sector Venous Outflow Reconstruction using Recipient's Superficial Femoral Vein in Adult Right Lobe Living Donor Liver Transplantation. (July 2018) - Kawachi, Shigeyuki; Obara, Hideaki; Chiba, Naokazu; Tomita, Koichi; Sano, Toru; Okihara, Masaaki; Gunji, Takahiro; Shinoda, Masahiro; Kitagawa, Yuko; Shimazu, Motohide
Abstract : Special attention must be paid in hepatic vein reconstruction to avoid outflow block in living donor liver transplantation (LDLT) with a right lobe graft. To reconstruct the middle hepatic vein (MHV) tributaries, the great saphenous vein, external iliac vein, and ovarian vein as well as portal vein or hepatic vein from the removed liver have been usually used as vein graft because of easy availability, however, these vessels had disadvantages regarding there caliber and length. The superficial femoral vein (SFV) has similar caliber as MHV and enough length (about 15cm) of SFV can be harvested from the recipient with no major complication. We decided to use SFV to reconstruct MHV tributaries in end-to-side anastomosis fashion during bench surgery. After anastomosis, SFV graft looked like MHV itself. For graft implantation, the donor right hepatic vein (RHV) was anastomosed to IVC at first, portal reconstruction was followed. After reperfusion, SFV graft was anastomosed to IVC on the left side of RHV anastomosis site. This technique was indicated in two cases of our LDLT. First case was 49-year-old male patient suffering from alcoholic liver cirrhosis. Both V5 and V8 tributaries were considered to be necessary to reconstruct by preoperative 3D simulation of perfusion area. Both V5 and V8 were reconstructed using SFV graft. Second case was 62-year-old male patient suffering from HBV cirrhosis and HCC. V5 tributary was reconstructed using SFV graft. All these tributaries have been patent excellently on 18 and 15 months after LDLT, respectively. MHV tributaries reconstruction using recipient's SFV might be feasible and effective method in LDLT.